The gift of Christmas - Leeson, Christine, 1965-; Hansen, Gaby. (London : Little Tiger Press, 2001)
Molly the mouse sets out to find a Christmas tree for her family. She "borrows" decorations for the tree from all the animals in the forest. The tree doesn't quite turn out like they want and they leave to go home but during the night Molly is in for a big surprize.
"Originally published as The Magic of Christmas."
Keywords: Christmas trees -- Juvenile fiction; Mice -- Juvenile fiction